A review of 16 years of quality control parameters at a mass‐rearing facility producing Queensland fruit fly, Bactrocera tryoni. Issue 2 (31st March 2014) - Fanson, B.G.; Sundaralingam, S.; Jiang, L.; Dominiak, B.C.; D'Arcy, G.
Abstract From 1996 to 2012, the mass‐rearing facility at Camden (NSW, Australia) has been producing Queensland fruit flies, Bactrocera tryoni (Froggatt) (Diptera: Tephritidae). During this time, the facility has regularly recorded fly quality parameters, creating a unique data set that provides an invaluable opportunity to evaluate the interrelationships among standard quality control (QC) parameters and test for redundant QC variables. Here, we conducted an exploratory data analysis to reveal relationships among the QC parameters. We found that pupal weight, adult lifespan, and longevity under nutritional stress (i.e., survival duration without food or water) had distinct monthly trends, suggesting that these QC parameters are sensitive to seasonal conditions. Furthermore, emergence percentage, flight ability, and adult lifespan were adversely affected by the dyeing/handling/irradiation process associated with sterile insect releases. Using a multivariate approach and controlling for monthly and yearly patterns, we showed that pupal weight and egg hatch are consistently negatively related and that percentage male and emergence rates are consistently negatively related. These results suggest that these correlation pairs measure similar quality information and hence one QC variable from each pair could be dropped. Flight ability was not strongly correlated with any of the QC variables, suggesting that this QC variable remains a useful QC metric. Finally, the longevity under nutritional stress QC appears to be fairly insensitive to QCs and we suggest that it should be replaced by the standard mortality under stress test.